Perfect tables : tabletop secrets, settings, and centerpieces for delicious dining - Yeoward, William (London, United Kingdom : Cico Books, 2011)
Perfect Tables showcases 26 stunning ideas for tables that will inspire you to entertain both on a grand scale and informally.
1. Special occasions -- 2. Family & friends -- 3. About color -- 4. Natural hues.
Includes index.
Keywords: TABLE SETTING AND DECORATION